Response of Bacterial and Fungal Soil Communities to Chinese Fir (Cunninghamia lanceolate) Long-Term Monoculture Plantations - Liu, Xian; Wang, Yuzhe; Liu, Yuhui; Chen, Hui; Hu, Yalin (Frontiers in Microbiology, 2020)
Successive rotation and monoculture, as common silvicultural practices, are extensively applied worldwide, particularly in subtropical Chinese fir (Cunninghamia lanceolata) plantations in southern China. Although regeneration failure and productivity decline are frequently observed in continuous monoculture plantations, the potential mechanisms are still unclear. In this study, high-throughput sequencing was used to compare the diversity and composition of bacterial and fungal communities among different generations of Chinese fir plantation (first rotation, FRP; second rotation, SRP; third rotation, TRP) and natural forest (NF) in December and June. Our results showed significant declines of richness and diversity of bacterial and fungal communities in TRP compared with FRP and SRP, but no significant difference between FRP and SRP. The fungal phyla with high relative abundance were Basidiomycota (12.9-76.9%) and Ascomycota (14.3-52.8%), while the bacterial phyla with high relative abundance were Acidobacteria (39.1-57.7%) and Proteobacteria (21.2-39.5%) in all treatments at both sampling months. On average, the relative abundance of Basidiomycota in TRP increased by 53.4%, while that of Ascomycota decreased by 37.1% compared with FRP and SRP. Moreover, soil NH4+-N, pH and DOC appear to be key factors in shaping the fungal communities while soil NH4+-N, DOCN and AP primarily drive the changes in bacterial communities. Collectively, our findings highlighted the alteration of soil bacterial and fungal communities induced by changes in soil nutrient environment in different generations of continuously-cultivated Chinese fir plantation.